CD81 Promotes a Migratory Phenotype in Neuronal-Like Cells. (4th February 2019) - Martins, Soraia A.; Correia, Patrícia D.; Dias, Roberto A.; da Cruz e Silva, Odete A.B.; Vieira, Sandra I.
Abstract: Tetraspanins, such as CD81, can form lateral associations with each other and with other transmembrane proteins. These interactions may underlie CD81 functions in multiple cellular processes, such as adhesion, morphology, migration, and differentiation. Since CD81's role in neuronal cells' migration has not been established, we here evaluated effects of CD81 on the migratory phenotype of SH-SY5Y neuroblastoma cells. CD81 was found enriched at SH-SY5Y cell's membrane, co-localizing with its interactor filamentous-actin (F-actin) in migratory relevant structures of the leading edge (filopodia, stress fibers, and adhesion sites). CD81 overexpression increased the number of cells with a migratory phenotype, in a potentially phosphatidylinositol 3 kinase (PI3K)–Ak strain transforming (AKT) mediated manner. Indeed, CD81 also co-localized with AKT, a CD81-interactor and actin remodeling agent, at the inner leaflet of the plasma membrane. Pharmacologic inhibition of PI3K, the canonical AKT activator, led both to a decrease in the acquisition of a migratory phenotype and to a redistribution of intracellular CD81 and F-actin into cytoplasmic agglomerates. These findings suggest that in neuronal-like cells CD81 bridges active AKT and actin, promoting the actin remodeling that leads to a motile cell morphology. Further studies on this CD81-mediated mechanism will improve our knowledge on important physiological and pathological processes such as cell migration and differentiation, and tumor metastasis.